2017
DOI: 10.1111/jce.13332
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of a novel mapping system combined with remote magnetic navigation in the catheter ablation of atrial fibrillation

Abstract: LA mapped by the novel system is stable and reliable. Combined with RMN, it could be effectively used for AF ablation without impacting overall procedural times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It is used as CARTO RMT™, together with the CARTO system and can be manipulated under 3D constructed cardiac imaging 592 . A method used in combination with the EnSite system has also recently been developed 593 …”
Section: Catheter Ablationmentioning
confidence: 99%
“…It is used as CARTO RMT™, together with the CARTO system and can be manipulated under 3D constructed cardiac imaging 592 . A method used in combination with the EnSite system has also recently been developed 593 …”
Section: Catheter Ablationmentioning
confidence: 99%
“…In both groups, RMN Niobe ES was used. The authors concluded that there were no significant differences in procedure parameters between the EnSite Precision and the CARTO ® 3; the overall procedure durations were 117.9±29.6 and 119.2±29.7 min, ablation times were 28.0±12.9 and 27.9±15.8 min, and fluoroscopy time were 6.1±2.4 and 4.8±2.2 min, respectively 26 .…”
Section: Discussionmentioning
confidence: 95%
“…Compared to current clinically available Sensei (Hansen Medical), Magellan (Hansen Medical), Niobe (Stereotaxis), and CGCI system (Magnetecs Inc), 4,5,7,8 our novel robotic system employs an open structure design and is compatible with current commercially available guidewires, catheters, ballons, and peripheral stent delivery systems. In addition, the novel robotic system accomplished multiple collaborative manipulations with 12 DOF, the manual operation could be stimulated with 4 robotic manipulators (each manipulator has 3 DOF—insertion/withdrawal, rotation, and clamping/releasing—which can achieve more complex operations compared to designed robotic systems with less DOF.…”
Section: Discussionmentioning
confidence: 99%